Predictive and experiential effects of STEAM-based CLIL on learners’ emotions, motivation, and efficacy - David Imamyartha (Studies in English Language and Education, 2026)
This research addressed the challenges to teaching Content and Language Integrated Learning (CLIL) and proposed that the STEAM approach (Science, Technology, Engineering, Arts, and Mathematics) could enhance CLIL teaching using a framework called 6Es (engage, explore, explain, engineer, enrich, and evaluate). The author first explained how STEAM could address some CLIL issues and showed that the 6Es aligned with the 4Cs (culture, content, cognition, and communication) of CLIL’s pluriliteracies approach. The author applied 6Es in a case study on 204 Indonesian tertiary students in 16-meeting CLIL lessons focusing on ecosystem protection, closely investigating their experiences using a set of instruments on a) multidimensional learning, b) academic emotion, c) academic control, d) science efficacy, e) language learning attitude and motivation, and f) learning reflection. The findings portrayed positive outcomes in the aforementioned dimensions, corroborated by a positive correlation between variables. The regression analysis substantiated the predictive power of self-directed learning, authentic problem solving, and creativity towards all key variables. Meaningful literacy practices were proven influential to the increment of learners’ self-regulation, allowing them to navigate and gain the utmost advantage of what would otherwise be seen as foreign language learning when presented in language pedagogy. Several pitfalls in the study, along with potential future inquiries, are also discussed.